Quality of life, control of treatment and satisfaction of patients with asthma in Bulgaria: a pilot study. Issue 1 (31st December 2022) - Doneva, Miglena; Milushewa, Petya; Dimitrova, Maria; Kamusheva, Maria; Stoitchkov, Jordan; Petrova, Guenka; Naydenova, Kremena; Krusheva, Borislava; Dimitrov, Vasil; Lakic, Dragana
Abstract: This study aims to evaluate clinical characteristics, quality of life and control of treatment and therapy satisfaction of patients with asthma in Bulgaria. A pilot study of Bulgarian patients with asthma selected by allergologists was performed. The predefined inclusion criteria were asthma diagnosis with at least 6 months of living with asthma and use of asthma medication. Patient characteristics, treatment, quality-of-life, control of asthma and therapy satisfaction were systematically assessed. A retrospective observational study was conducted among asthma patients in Sofia in 2019. A strict definition of asthma-based solely on physicians' diagnosis was used. Allergologists from two national reference hospitals for asthma therapy selected asthma patients. Every third patient with asthma that visited the office within 5 months period, and that agreed to participate was selected for the study. Quality-of-life of patients was measured using the EQ5D Assessment Test, control of asthma was assessed using ATCQ and ATC tests. A total of 71 asthma patients were enrolled. Approximately 43.6% were male, 16.9% were smokers, occupational risk factors were low (4.22%), 25% had moderate and 38% had severe asthma. The mean scores of asthma control treatment were 16.92 ± 5.68. The group has relatively high percentages of severe asthma patients. The asthma was not well controlled. National asthma strategies should focus on prevention and early detection of the disease.